Skrining hiv pada wanita hamil: scoping review - pratami, yustika rahmawati; hasnia; Utami, Arum Surya; Lestari, Tiyan Febriyani; Lestari, Susi; Putri, Harlinda Widia (Jurnal Kesehatan, 2024)
Many pregnant women still do not undergo HIV screening, which is a problem both in Indonesia and internationally. Objective to explore HIV screening in pregnant women. Method scoping review using the PRISMA-ScR checklist framework and selected with inclusion and exclusion criteria. This literature review has screened articles from three databases totaling 1,070 articles, then 10 selected articles were found. Furthermore, the author found themes in this literature review, including HIV test results in pregnant women and two of the themes were factors related to HIV screening in pregnant women, namely socio-demographic factors and health factors. Conclusion: The researcher concluded that the incidence of HIV is high in developing countries. Gender issues were also found in this literature review that many HIV screening services only focus on pregnant women. Furthermore, the findings also stated that pregnant women who live with their partners are still actively having sexual relations can be a factor in the occurrence of new cases.